Meningkatkan Nilai Tambah Jaringan Irigasi dengan Pembangkit Listrik Tenaga Mikro Hidro (Studi Kasus – Ji Kedung Kandang) - Suwignyo Suwignyo; Khoirin Nissa; Azhar Adi Darmawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The development of Micro Hydro Power Plants (PLTMH) in irrigation networks has great potential to contribute to the national electricity supply. However, the construction of the PLTMH in the irrigation network is still constrained due to the design of the placement of civil buildings which are limited by land. In fact, the procurement of electrical energy in the irrigation network can help provide backup sources of electrical energy based on New and Renewable Energy (EBT) which can also play a role in reducing Greenhouse Gas (GHG) emissions. Based on a study in the main irrigation canal of Kedung Kandang which has a fall height of 11 m with a flow of 3.5 m3/second, the generating power that can be generated reaches 275 kW. Conveyor channel design and reservoir ponds are planned in the channel body. The dimensions of the reservoir are planned to have a water depth (h) = 3.2 m, a width of 2.5 m, and a length of 10 m. Based on the study of determining the type of turbine, the components used are two propeller turbines of the H-Shaft type with a diameter of 0.603 m, each with a capacity of 137.5 kW. The use of two turbines requires a power house design measuring 4.5 x 6.5 m. The potential results of PLTMH in the Kedung Kandang main irrigation canal can be utilized to meet the electrical energy needs of SMK Muhammadiyah 7 and Pondok Pesantren Muhammadiyah Gondanglegi as well as an integrated field laboratory between SMK Muhammadiyah 7 and University of Muhammadiyah Malang. By utilizing NRE-based electricity sources, it is estimated that it will be able to reduce carbon emissions from the use of fossil energy and coal.